Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am working through the following problem, but finding it hard to know where to go.

Using the Divergence theorem and the following identities

$\nabla \cdot (A \times B) = B\cdot(\nabla \times A) - A\cdot(\nabla \times B)$

$\nabla \times (\nabla \times A) = \nabla (\nabla \cdot A) - \nabla ^2 A$

In a volume V, enclosed by a surface S, the vector fields X and Y satisfy the coupled equations

$\nabla \times \nabla \times X = X+Y$

$\nabla \times \nabla \times Y = Y-X$

If the values of $\nabla \times X$ and $\nabla \times Y$ are given on S, show that X and Y are unique in V.

I am assuming that I need to show that $\nabla ^2 X$ and $\nabla ^2 Y$ are equal to zero and that X and Y are zero on S to satisfy the uniqueness theorem for Poisson's equation. But am unsure of a good way to get there, so before I write my scribbles if someone could point me in the write direction it would be great.

Any help, pointing in the right direction would be very helpful.

EDIT: Fixed the second expression, original didn't make sense.

share|cite|improve this question

With this I am not even sure what the question is
but here is the answer I give to prove $X \neq Y$:

Sum the two equations $$2Y = \nabla \times \nabla \times X + \nabla \times \nabla \times Y$$ Subtract the two equations $$2X = \nabla \times \nabla \times X - \nabla \times \nabla \times Y$$

Using $\nabla \times \nabla \times A = \nabla(\nabla \cdot A) - \nabla^2 A$ \begin{align} 2Y &= \nabla(\nabla \cdot X) − \nabla ^2 X + \nabla(\nabla \cdot Y) − \nabla ^2 Y\\ 2Y &= \nabla\big(\nabla \cdot(X+Y)\big) − \nabla ^2 (X+Y) \end{align} and then resub $\nabla \times \nabla \times X = X+Y$ $$ 2Y = \nabla\big(\nabla \cdot (\nabla \times \nabla \times X)\big)− \nabla ^2 (\nabla \times \nabla \times X) $$ similarly $$ -2X = \nabla\big(\nabla \cdot (\nabla \times \nabla \times Y)\big) − \nabla ^2 (\nabla \times \nabla \times Y) $$

Therefore if $X=Y$ $$\nabla \times X = -\nabla \times Y$$ which implys $Y=0$ and $X=0$.

Therefore $X = Y$ only in trivial case.

share|cite|improve this answer
The question says nothing about whether $X=Y$. And of course if $X=Y$, from the right sides of the two equations we'd have $X+Y=Y-X$, which implies $X=0$. – Robert Israel Nov 13 '12 at 22:34
$\large X + Y = \nabla{\rm f}$. – Felix Marin Sep 22 '13 at 1:43

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.